2017
DOI: 10.1111/apt.14421
|View full text |Cite
|
Sign up to set email alerts
|

Exposure‐response relationship of certolizumab pegol induction and maintenance therapy in patients with Crohn's disease

Abstract: SummaryBackgroundTherapeutic drug monitoring may optimize therapy for Crohn's disease (CD).AimTo use a population pharmacokinetic model that accounts for the time‐varying nature of covariates to simulate certolizumab pegol (CZP) concentrations to evaluate the exposure‐response relationship for CZP in Crohn's disease.MethodsAdults (N = 2157) with Crohn's disease were treated with CZP in nine clinical trials. Simulated CZP concentrations were compared to outcomes at weeks 6 and 26, including Crohn's disease acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 30 publications
2
25
0
1
Order By: Relevance
“…Vande Casteele et al also demonstrated, based on multivariable analyses, that higher CZP concentrations at week 6 were associated with composite remission at week 6 and most importantly week 26, suggesting that early post‐induction anti‐TNF drug monitoring can predict long‐term therapeutic outcomes in IBD . These findings are consistent with previous data reporting that higher post‐induction infliximab concentrations at week 14 are associated with higher rates of clinical response or remission at week 54 and less treatment failure or colectomy .…”
supporting
confidence: 74%
See 3 more Smart Citations
“…Vande Casteele et al also demonstrated, based on multivariable analyses, that higher CZP concentrations at week 6 were associated with composite remission at week 6 and most importantly week 26, suggesting that early post‐induction anti‐TNF drug monitoring can predict long‐term therapeutic outcomes in IBD . These findings are consistent with previous data reporting that higher post‐induction infliximab concentrations at week 14 are associated with higher rates of clinical response or remission at week 54 and less treatment failure or colectomy .…”
supporting
confidence: 74%
“…Vande Casteele et al have performed the largest combined exposure‐response analysis of any anti‐TNF agent to date and evaluated the association of CZP exposure with clinical and biomarker outcomes in patients with Crohn's disease (CD). They used pooled data from nine clinical trials and a refined population pharmacokinetic model that accounts for the time‐varying nature of covariates to simulate CZP concentrations at exact time points in individual patients .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure‐response metrics have increasingly been used to optimise IBD treatment with anti‐TNFα agents, but the vast majority of the reported analyses were based on studies not prospectively designed from exposure‐response inferences or adjusted for potential confounding factors . In fact, only recently was the first study with patient‐level covariate adjustment of the exposure‐response relationship for anti‐TNFα therapy published, by Vande Casteele et al, in patients with CD treated with certolizumab pegol. Very limited data on the vedolizumab exposure‐response relationship are currently available to guide clinicians.…”
Section: Discussionmentioning
confidence: 99%